A High Resolution Radiation Hybrid Map of Wheat Chromosome 4A - Balcarkova, B.; Frenkel, Z.; Skopova, M.; Abrouk, M.; Kumar, A.; Chao, S. M.; Kianian, S. F.; Akhunov, Eduard; Korol, A. B.; Dolezel, J.; Valarik, M. (My University, 2017)
Bread wheat has a large and complex allohexaploid genome with low recombination level at chromosome centromeric and peri-centromeric regions. This significantly hampers ordering of markers, contigs of physical maps and sequence scaffolds and impedes obtaining of high-quality reference genome sequence. Here we report on the construction of high-density and high-resolution radiation hybrid (RH) map of chromosome 4A supported by high-density chromosome deletion map. A total of 119 endosperm-based RH lines of two RH panels and 15 chromosome deletion bin lines were genotyped with 90K iSelect single nucleotide polymorphism (SNP) array. A total of 2316 and 2695 markers were successfully mapped to the 4A RH and deletion maps, respectively. The chromosome deletion map was ordered in 19 bins and allowed precise identification of centromeric region and verification of the RH panel reliability. The 4A-specific RH map comprises 1080 mapping bins and spans 6550.9 cR with a resolution of 0.13 Mb/cR. Significantly higher mapping resolution in the centromeric region was observed as compared to recombination maps. Relatively even distribution of deletion frequency along the chromosome in the RH panel was observed and putative functional centromere was delimited within a region characterized by two SNP markers.
Citation: Balcarkova, B., Frenkel, Z., Skopova, M., Abrouk, M., Kumar, A., Chao, S. M., . . . Valarik, M. (2017). A High Resolution Radiation Hybrid Map of Wheat Chromosome 4A. Frontiers in Plant Science, 7, 14. https://doi.org/10.3389/fpls.2016.02063
Keywords: Endosperm Radiation Hybrid Panel; Radiation Hybrid Map; Wheat Chromosome; 4A; Chromosome Deletion Bin Map; Triticum Aestivum